PERANCANGAN ENTERPRISE ARCHITECTURE PENJUALAN DIGITAL MENGGUNAKAN ZACHMAN FRAMEWORK DI CV PUTRA WIBAWA - Muhamad Abdan Shakuro; TutI Rohayati; Dadan Mulyana (Jurnal Mahasiswa Sistem Informasi Galuh, 2026)
CV Putra Wibawa, a distribution company, currently still relies on a manual system for recording transactions and its sales processes. This condition has led to significant operational challenges, such as delays in information, inefficiencies in time and resources, and a limited market reach. Therefore, this research aims to design a comprehensive enterprise architecture to support the implementation of digital sales by utilizing the Zachman Framework.The Zachman Framework was chosen due to its ability to provide a structured and holistic system representation. This framework analyzes six fundamental aspects: what, how, where, who, when, and why, from six different stakeholder perspectives, ranging from the planner, owner, designer, builder, subcontractor, to the functioning system. The research method applied was qualitative, where data was collected through direct observation and in-depth interviews with key parties in the company.The analysis ultimately resulted in a strategic information system design. This design is capable of providing core features such as integrated transaction recording, an easily accessible digital product catalog, and support for online payments. It is hoped that the implementation of this system will subsequently improve overall operational efficiency, expand the reach of sales to a broader market, and ultimately enhance the company's competitiveness in the digital era.